Adaptable secure communication for the Cloud of Things. (3rd October 2016) - Vasić, Valter; Antonić, Aleksandar; Pripužić, Krešimir; Mikuc, Miljenko; Žarko, Ivana Podnar
Summary: Cloud of Things (CoT) is a novel concept driven by the synergy of the Internet of Things (IoT) and cloud computing paradigm. The CoT concept has expedited the development of smart services resulting in the proliferation of their real world deployments. However, new research challenges arise because of the transition of research‐driven and proof‐of‐concept solutions to commercial offerings, which need to provide secure, energy‐efficient, and reliable services. An open research issue in the CoT is to provide a satisfactory level of security between various IoT devices and the cloud. Existing solutions for secure CoT communication typically use devices with pre‐loaded and pre‐configured parameters, which define a static setup for secure communication. In contrast to existing pre‐configured solutions, we present an adaptable model for secure communication in CoT environments. The model defines six secure communication operations to enable CoT entities to autonomously and dynamically agree on the security protocol and cryptographic keys used for communication. Further on, we focus on device agreement and present an original solution, which uses the Agile Cryptographic Agreement Protocol in the context of CoT. We verify our solution by a prototype implementation of CoT device agreement based on required security level, which takes into account the capabilities of communicating devices. Our experimental evaluation compares the average processing times of the proposed secure communication operations demonstrating the viability of the proposed solution in real‐world deployments. Copyright © 2016 John Wiley & Sons, Ltd.